Rocky! The Left-Wing Theatre Ghetto’s Auto-Knock-Out - Daugaard, Solveig (Peripeti, 2023)
Text and direction: Tue Biering. Scenography: Peter Schultz. Sound design: Ditlev Brinth. Lighting design, realisation: Mathilde Niemann Hüttel. Cast: Morten Burian Cheanne Nielsen and Kasper Frederik Mortensen.